The Emerging Project Bond Market : Covenant Provisions and Credit Spreads - Dailami, Mansoor; Hauswald, Robert (World Bank, Washington, DC, 2014)
The emergence in the 1990s of a nascent project bond market to fund long-term infrastructure projects in developing countries merits attention. The authors compile detailed information on a sample of 105 bonds issued between January 1993 and March 2002 for financing infrastructure projects in developing countries, document their contractual covenants, and analyze their pricing determinants. They find that on average, project bonds are issued at approximately 300 basis points above U.S. Treasury securities, have a surprisingly high issue size of US$278 million, a maturity of slightly under 12 years, and are rated slightly below investment grade. In terms of geographic origin, projects in Asia and Latin America have issued more bonds than those located in other regions. Much of the recent work relating to the role of contractual covenants to the determination of bond prices has focused on the U.S. corporate bond market with its unique bankruptcy code - Chapter 11 - and well developed legal framework, recognizing the bond contract as the sole instrument of defining the rights and duties of various parties. In circumstances in which the underpinning legal and institutional frameworks governing contract formation and enforcement are not well developed, the link between bond pricing and legal framework becomes important. This finding is confirmed by the authors' econometric analysis of project bond pricing model. So, investors take into account the quality of the host country's legal framework and reward projects located in countries that adhere to the rule of law with tighter credit spreads and lower funding costs.